A tale of two vulvar angiomyxomas: Two cases and review of literature - Anastasia Navitski; Leslie Adams; Bogna N. Brzezinska; Jessa Suhner; Taylor Sliker; Pramila Moideen; Amanda Barrett; Abdul R. Abualruz; Marian S. Johnson; Bunja Rungruang (Elsevier, 2023)
Vulvar angiomyxomas are rare benign mesenchymal neoplasms. Superficial and Aggressive angiomyxomas are two distinct phenotypes that present similarly to other more common vulva-perineal pathologies. Albeit both angiomyxomas carry a risk of recurrence, especially in the setting of incomplete resection, simple excision is insufficient for Aggressive angiomyxoma. It requires wide local excision because of its unique potential for local invasion, infiltration of the paravaginal and pararectal tissue, and more distant metastasis. Here, we present a case of Superficial angiomyxoma and a case of Aggressive angiomyxoma to highlight the diagnostic challenges and management strategies of each tumor. In both cases, angiomyxomas were initially misdiagnosed because of their rarity and nonspecific presentation. Magnetic resonance imaging is the modality of choice for evaluation due to inherent higher spatial resolution of soft tissue anatomical details. Early diagnosis of Aggressive angiomyxoma can prevent incomplete excision and recurrence, spare additional surgery, and offer hormonal therapy options.